Note on the occurrence of the White-winged Wood Duck Cairina scutulata on the west coast of North Sumatra - Holmes, Derek A (KUKILA, 1990)
Details are provided of records of Cairina scutulata from North-western Sumatra. These are the first reports of this endangered species from outside the South-eastern corner of Sumatra since 1909, and they greatly expand the range in which remnant populations may still occur.